No Differences in Active Young Adults' Affective Valence or Enjoyment Between Rowing and Cycling. Issue 3 (June 2020) - Astorino, Todd A.; Oriente, Chandler; Peterson, Jill; Alberto, Giannina; Castillo, Erica Elena; Vasquez-Soto, Ulices; Ibarra, Esmerelda; Guyse, Victoria; Castaneda-Garcia, Ivan; Marroquin, Joel R.; Dargis, Rachel; Thum, Jacob
Regular participation in continuous exercise modalities including running, walking, cycling, and rowing is an effective way to satisfy public health recommendations for moderate intensity continuous training. Rowing and cycling are each nonweight bearing, yet they differ, based on the size of muscle mass required. As it is unknown whether this discrepancy alters participants' perceptual responses to exercise, this study examined differences in affective valence and enjoyment between rowing and cycling. Active men and women ( N = 22; M age = 27.4, SD =7.7 years; M body mass index = 23.6, SD = 2.8 kg/m 2 ) initially performed incremental exercise on the cycle ergometer and rowing ergometer to assess maximal oxygen uptake. During two subsequent sessions, they performed 30 minutes of graded exercise on either modality at intensities equal to 60-65%, 70-75%, and 80-85% maximal heart rate, during which we measured affective valence (Feeling Scale), rating of perceived exertion (RPE: 6–20), and enjoyment. Results showed a significant increase in RPE ( p < .001) and decrease in affective valence ( p < .001) during exercise, but no difference in RPE, affective valence, or enjoyment in response to cycling versus rowing. In total, nine participants preferred cycling to rowing, while 13 preferred rowing to cycling. Overall, rowing and cycling elicit similar changes in RPE, affective valence, and enjoyment. Future work is needed to assess the applicability of these findings to larger and more diverse populations.